Reliability of tests for speed and agility assessment in cadet basketball player - Lukic, M.; Petrovic, A.; Copic, N.; Petronijevic, S.; Jovanovic, S. (Facta Universitatis: Series Physical Education and Sport, 2020)
The aim of this research is to determine whether the Illinois test (IL), T-test (Tt), 4x5m Shuttle run (4x5m), 20 m Sprint (S20m), 10 m Sprint (S10m) are reliable tests in assessing the speed and agility of cadet basketball players. The strategy of this research involved a traditional quantitative approach to research with a correlation studies design. The total sample consisted of 38 male participants. The mean age of the participants was -AGE=16.03 years, body height-BH=183.5 cm; body mass-BM=74.1 kg; Body Mass Index-BMI=22.08 kg/m2. The most reliable agility test when performing without a ball is ILNB, while less reliable are TtNB and the 4x5mNB, both without a ball. A reliable test that is performed without a ball to assess the speed of a cadet basketball player is the S10mNB. On the other hand, all speed and agility tests when performed with a ball are reliable for testing cadet basketball players. The proposed speed and agility tests have proven to be reliable for cadet basketball players.